Pengaruh Jenis dan Dosis Pupuk Kandang terhadap Pertumbuhan dan Hasil Tanaman Kacang Buncis (Phaseolus vulgaris L.) - Aloysius Usboko; Maria Afnita Lelang; Eduardus Yosef Neonbeni (Fakultas Pertanian, Universitas Timor, 2017)
Research to determine the effect of type and dosage of manure on the growth and yield of french bean and also type and dosage of manure that can increase growth and yield, implemented in December 2016 - February 2017 in the experimental garden of the Faculty of Agriculture, Timor University, Sasi Village. The research used Randomized Block Design with two factors, namely, the first factor is the type of manure, consisting of cow manure, pig manure, goat manure. The second factor is the dosage of manure, consisting of 5 t / ha, 10 t / ha, 15 t / ha. The results showed no interaction between the type and dosage of manure. Giving of pig manure with the dosage of 15 t / ha can give the highest growth, ie at the end of vegetative reaching height 56,78 cm and highest yield in the form of, number of pods per plant most (39 pods), number of fresh pods per plot (235 pods) , fresh pods per heaviest plant (240 g), and fresh pods per heaviest plot (1.28 kg).